Determination of antioxidant and antimutagenic activities of Phlomis armeniaca and Mentha pulegium - Onder YUMRUTAS, Saadet D. SAYGIDEGER (Journal of Applied Pharmaceutical Science)
This study was designed to determine antioxidant and antimutagenic activities of methanol and n-hexane extracts of Phlomis armeniaca and Mentha pulegium and their phenolic compounds. The extracts were screened for their possible antioxidant and antimutagenic activities by DPPH and ABTS free radical scavenging, reducing power, metal chelating and DNA nicking assays. The methanol extracts of the plants exhibited significant antioxidant activities determined by different assays. P. armeniaca showed higher activities in antioxidant assays. Also, the highest phenolic content was observed in P. armeniaca. In DNA nicking assay (antimutagenic), all extracts of these plants (20-40 Î¼g/mL) exhibited DNA protecting activities. This study shows that methanol extracts of the plants have higher antioxidant activities than their hexane extract. Moreover, the plants can be used as natural antioxidants and antimutagenic sources.
Keywords: Phlomis armeniaca, Mentha pulegium, Antioxidant/antimutagenic activity, phenolic compounds, flavonoid, flavonol.